2011
DOI: 10.1111/j.1399-3062.2011.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Trichosporon fungemia in a patient with refractory acute myeloid leukemia using voriconazole combined with liposomal amphotericin B

Abstract: Trichosporon fungemia is a rare and fatal fungal infection that occurs in patients with prolonged neutropenia associated with hematologic malignancies. A 21-year-old male developed Trichosporon fungemia during remission induction therapy for acute myeloid leukemia (AML). Although two courses of induction therapy failed to induce a remission of AML, combination therapy with voriconazole and liposomal amphotericin B (L-AmB) followed by monocyte colony-stimulating factor ameliorated the Trichosporon fungemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
3
11
0
1
Order By: Relevance
“…In that study, resolution of infection was significantly associated with neutrophil recovery [3] . Hosokawa K et al reported in 2011 on a patient recovering from Trichosporon asahii fungemia before neutrophil recovery after a combination therapy with voriconazole and liposomal amphotericin B, as in our case [16] . The patient eventually died of acute myeloid leukemia but the combination therapy was effective enough to allow subsequent chemotherapies and allogeneic stem cell transplantations [16] .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In that study, resolution of infection was significantly associated with neutrophil recovery [3] . Hosokawa K et al reported in 2011 on a patient recovering from Trichosporon asahii fungemia before neutrophil recovery after a combination therapy with voriconazole and liposomal amphotericin B, as in our case [16] . The patient eventually died of acute myeloid leukemia but the combination therapy was effective enough to allow subsequent chemotherapies and allogeneic stem cell transplantations [16] .…”
Section: Discussionsupporting
confidence: 62%
“…Hosokawa K et al reported in 2011 on a patient recovering from Trichosporon asahii fungemia before neutrophil recovery after a combination therapy with voriconazole and liposomal amphotericin B, as in our case [16] . The patient eventually died of acute myeloid leukemia but the combination therapy was effective enough to allow subsequent chemotherapies and allogeneic stem cell transplantations [16] . Trichosporon faecale is rarely reported in humans and almost always in localized infections [1,5,8–10] .…”
Section: Discussionsupporting
confidence: 62%
“…However, variations in susceptibility in vitro may suggest that not all species and isolates are equally susceptible to this agent [257]. Voriconazole is the preferred agent because it displays good in vitro activity against most Trichosporon species and isolates and has been associated with good in vivo outcome in most cases of clinical and animal studies [232,233,256,261,263,[269][270][271]. In addition to triazole treatment, resolution of myelosuppression and removal of vascular catheters are other confounders related with increased survival [28,192,231,237,238].…”
Section: Susceptibility Testing and Treatmentmentioning
confidence: 99%
“…As high MIC values correspond to low response rates in hematological patients receiving amphotericin B [51] or an echinocandin [17, 53, 105], these agents cannot be recommended as monotherapy (DIII). Clinical data to recommend these agents in combination therapy with each other or with an azole are too scarce to establish any recommendation [14, 51, 71]. …”
Section: Treatment Of Trichosporon Infectionsmentioning
confidence: 99%